Telecommunications infrastructure and economic development: a simultaneous approach - Lars-Hendrik Röller; Leonard Waverman (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
In this paper we investigate how telecommunications infrastructure affects economic growth. This issue is important and has received considerable attention in the popular press concerning the creation of the information superhighway and its potential impacts on the economy. We use evidence from 21 OECD countries over the past twenty years to examine the impacts that telecommunications developments may have had. We estimate a structural model which endogenizes telecommunication investment by specifying a micro-model of supply and demand for telecommunication investments. The micromodel is then jointly estimated with the macro-growth equation. After controlling for country-specific fixed effects, we find evidence of a positive causal link, provided that a critical mass of telecommunication infrastructure is present. – – In diesem Beitrag wird untersucht, welchen Einfluß die Telekommunikations-Infrastruktur auf die wirtschaftliche Entwicklung ausübt. Diese wichtige Frage hat im Zusammenhang mit der Diskussion um Informationsautobahnen Aktualität erlangt. In der vorliegenden Studie wird der Einfluß der Telekommunikations-Infrastruktur für 21 OECDLänder für die vergangenen 20 Jahre analysiert. Es wird ein Strukturgleichungsmodell geschätzt, in dem Investitionen in die Telekommunikations-Infrastruktur als endogene Variable erfaßt werden und in einem Mikromodell Angebot und Nachfrage nach Telekommunikations- Investitionen spezifiziert werden. Das Mikromodell wird dann zusammen mit der Makro-Wachstumsgleichung geschätzt. Als Ergebnis stellen die Autoren dann eine positive Kausalbeziehung zwischen Telekommunikations-Investitionen und wirtschaftlicher Entwicklung fest, wenn eine kritische Masse an Telekommunikations- Infrastruktur existiert.
Keywords: 330